Disentangling the Influences of Leaders' Relational Embeddedness on Interorganizational Exchange - Barden, Jeffrey Q.; Mitchell, Will (Academy of Management Journal, 2007)
Drawing on the concept of relational embeddedness and the associated mechanisms of mutual understanding, trust, and commitment, we examine how leaders' prior exchange experiences influence the likelihood of subsequent interorganizational exchange. We begin to develop a microlevel model of organization-level relations that accounts for nodal multiplexity. In data on baseball player trades, we found that individual leaders' ties affected exchanges less than did an organization's other ties. The sharing of exchange experiences by organizations and their current leaders increased the influences of those experiences on exchange behavior. Thus, leaders have more influence within their organizational contexts than in isolation.